2020
DOI: 10.1021/acsapm.9b01007
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Morphological Properties of Lignin-Based Thermosets

Abstract: The need for renewable alternatives for fossil-based aromatic material constituents is evident for a more sustainable society. Lignin is the largest source of naturally occurring aromatic compounds but has mainly been considered as waste material or energy source in the pulp and paper industry. Developments in extracting lignin from these processes provide a large source for renewable aromatic structures to be used in various applications. Producing thermosets out of lignin is a very promising route to utilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 45 publications
4
77
0
2
Order By: Relevance
“…The lignin fraction could be used directly as a polymer precursor for material synthesis or catalytically depolymerized to platform monomers. Based on their functionality, structure, low DP n and demonstrably narrow Đ , these lignins might be suitable as polymer precursors for the synthesis of thermosetting resins, as shown in recent studies . In those cited studies, oligomeric fractions were shown to be preferable to polymeric fractions for the synthesis of homogeneous materials, due to their mutual solubility with other chemical components used in the synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…The lignin fraction could be used directly as a polymer precursor for material synthesis or catalytically depolymerized to platform monomers. Based on their functionality, structure, low DP n and demonstrably narrow Đ , these lignins might be suitable as polymer precursors for the synthesis of thermosetting resins, as shown in recent studies . In those cited studies, oligomeric fractions were shown to be preferable to polymeric fractions for the synthesis of homogeneous materials, due to their mutual solubility with other chemical components used in the synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…The thiol-ene reaction has been applied with terpenes as starting resins for 3D printing technologies [104] and, in general, to the preparation of thermosetting materials from renewable materials such as lignin [105,106], eugenol [107,108], furan derivatives [109], allylated aminoacids The main drawbacks of thiol-ene chemistry are the strong odor of thiols, limited shelf life, low glass transition temperatures and poor mechanical properties, such as hardness, mainly due to the structure of the thiols used [102]. The use of thiolactones has been proposed to circumvent some of these problems [103].…”
Section: Scheme 9 Possible Termination Reaction During Thiol-ene Promentioning
confidence: 99%
“…The thiol-ene reaction has been applied with terpenes as starting resins for 3D printing technologies [104] and, in general, to the preparation of thermosetting materials from renewable materials such as lignin [105,106], eugenol [107,108], furan derivatives [109], allylated aminoacids [110] and resveratrol [111]. Keratin, which is a natural polymer found in hair and nails, contains thiols in its cysteine and methionine structures; as such, it has been used as a renewable natural reinforcing agent for photocured thiol-ene coatings [112].…”
Section: Scheme 9 Possible Termination Reaction During Thiol-ene Promentioning
confidence: 99%
“… [7–9] As such, lignin is used as a solid fuel for combustion. More recently, researchers are developing composite polymeric materials from lignin; which can be used as a UV‐blocking agent [10–12] …”
Section: Introductionmentioning
confidence: 99%